The Rhetorical Strategy of 1 Timothy - O'Donnell, Tim (The catholic biblical quarterly, 2017)
Although 1 Timothy can appear loosely organized, the letter has a coherent rhetorical strategy that adapts conventions from a variety of literary forms, including household and station codes, protreptic letters, and panegyric. Three interconnected formal patterns are woven consistently through the text. Pervasive antitheses between true and false doctrine, virtue and vice evoke an overall atmosphere of crisis. Pairs of examples, presenting persons in unequal social relations, exhort a role-differentiated community to ordered conduct. An ABAB alternating pattern of precept and example binds the letter into a coherent but flexible structure and shows true belief and right behavior reinforcing each other in a unified response to the crisis.